2018
DOI: 10.1111/cns.13050
|View full text |Cite
|
Sign up to set email alerts
|

Early compensatory responses against neuronal injury: A new therapeutic window of opportunity for Alzheimer's Disease?

Abstract: Alzheimer's disease (AD) is characterized by extensive neurodegeneration and inflammation in selective brain areas, linked to severely disabling cognitive deficits. Before full manifestation, different stages appear with progressively increased brain pathology and cognitive impairment. This significantly extends the time lag between initial molecular triggers and appearance of detectable symptoms. Notably, a number of studies in the last decade have revealed that in the early stage of mild cognitive impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 124 publications
3
42
0
Order By: Relevance
“…A transient rise in the CSF levels of these synaptic proteins may occur as an early event in AD, followed by continual decreases along with disease progression 26 . This finding is supported by previous biological studies showing that a pathway compensating for synaptic damage increased the sizes of vesicles and synapses during the early stage of AD 27 .…”
Section: Discussionsupporting
confidence: 87%
“…A transient rise in the CSF levels of these synaptic proteins may occur as an early event in AD, followed by continual decreases along with disease progression 26 . This finding is supported by previous biological studies showing that a pathway compensating for synaptic damage increased the sizes of vesicles and synapses during the early stage of AD 27 .…”
Section: Discussionsupporting
confidence: 87%
“…Our findings advance the current understanding of FDG-PET changes in MCI, providing an explanatory model of FDG-PET hypermetabolism that has been observed in multiple studies in asymptomatic and symptomatic elderly subjects (for a review, see [28]). In line with our results, a recent study in MCI reported increased FDG-PET metabolism at low levels of amyloid-PET but not high levels of amyloid-PET [7].…”
Section: Discussionsupporting
confidence: 66%
“…We have recently suggested that microglia may represent a feasible target for early intervention in different neuroinflammatory conditions [32][33][34]. Importantly, melatonin was shown to inhibit microglial pro-inflammatory polarization in hypoxic conditions in animal models [35][36][37].…”
Section: Introductionmentioning
confidence: 99%